Menjaga Tradisi Minum Jamu Madura Dengan Penyampaian Pesan Interpersonal Kesehatan Antara Peramu Dan Pengguna - Ekna Satriyati (DIMENSI - Journal of Sociology, 2017)
The tradition of drinking herbal medicine is an effort to maintain body and mind health and to cure diseases based on local knowledge of the Madurese community. This study aims to describe efforts to maintain the tradition of drinking herbal medicine through the delivery of interpersonal messages between the maker to the user. The research used qualitative phenomenon-based herbal drinking tradition with data collection through observation and interview to informants and analyzed to get meaning about the form of interpersonal message delivery. The study found the form of interpersonal messages in the form of delivery of herbal products with health issues, disease complaints, prevent and overcome the disease. The profound meaning of cultural messages is the motivation to balance physical and mental health.